The Clinical Course and Outcomes of Familial Mediterranean Fever in Crimean Tatar Patients: Preliminary Results of Case Series - Olga V. Zhogova; Sergey V. Ivanovskiy; Natalya V. Lagunova; Anastasia V. Tumakova; Mikhail M. Kostik (Вопросы современной педиатрии, 2020)
Background. Familial Mediterranean fever (FMF) is the most common monogenic autoinflammatory disease. It is more typical among Turks, Jews, Armenians, Arabs and nationalities permanently living in the Mediterranean area. Crimean Tatars were not considered as the population where FMF may occur until 2016. Objective. The aim of the study was to describe the clinical course and outcomes of familial Mediterranean fever in Crimean Tatar children. Methods. We have studied data from medical records of children under the age of 18 with the diagnosis of FMF verified according to the Eurofever/PRINTO 2019 criteria. The illness onset characteristics were estimated on the last admission to the hospital, as well as aspects of management. Results. The median age of FMF diagnosis was 9.5 (4; 14) years, time from the first clinical manifestations to diagnosis establishment was 5.5 (2; 9) years. The primary clinical manifestations of SSL were fever and arthritis (n = 16), erysipelas rashes (n = 9/16), peritonitis (n = 8/16), pleurisy (n = 1/17). All patients had knee arthritis, and 4/16 had hip arthritis. 12 children with FMF at debut were diagnosed as acute respiratory infection, 2 — as teething, 2 — as juvenile arthritis. The M694V variant of MEFV gene were revealed in 14/16 patients (3 in homozygous state), M680I and V726A variants were revealed once each. Parents of 8/16 patients were near related (cousins and second cousins). Colchicine intolerance was diagnosed in 2/16 patients, resistance — in 4/16 patients. Genetically engineered biologic drugs (GEBD) were prescribed for 6 patients (canakinumab in 4 cases, tocilizumab in 2 cases). Colchicine and/or GEBD therapy was effective in all patients (lesser frequency, duration and severity of episodes; improvement of laboratory signs of disease activity). Conclusion. Heterozygous pathological variant M694V of MEFV gene is the most common among Crimean Tatar patients with FMF, when the most frequent clinical signs are fever and arthritis. Every third patient has received GEBD therapy. This therapy was effective in all cases.